2021
DOI: 10.1029/2020jb021325
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation Creep of Olivine: Backstress Evolution Controls Transient Creep at High Temperatures

Abstract: The evolution of viscosity during flow of mantle rocks at high temperatures is fundamental to a variety of geodynamic processes. For example, transient creep of the upper mantle has been identified as a major contributor to geodetically observed surface deformations during post-seismic creep (Freed et al., 2012;Masuti et al., 2016;Pollitz, 2005;Qiu et al., 2018), for which the strains are typically <10 −3 , and inferred viscosities are one to two orders of magnitude lower than the long-term, steady-state visco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(81 citation statements)
references
References 100 publications
(238 reference statements)
3
68
0
Order By: Relevance
“…For clarity, we emphasize that residual stress heterogeneity is the physical manifestation of long‐range dislocation interactions, which generate back stress as an emergent state variable (Hansen et al., 2021; Wallis et al., 2020). It is difficult to infer the magnitude of former back stress directly from observations of stress heterogeneity, but the presence of long‐range stress heterogeneity imparted by the dislocations does demonstrate the mechanism by which back stress can emerge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For clarity, we emphasize that residual stress heterogeneity is the physical manifestation of long‐range dislocation interactions, which generate back stress as an emergent state variable (Hansen et al., 2021; Wallis et al., 2020). It is difficult to infer the magnitude of former back stress directly from observations of stress heterogeneity, but the presence of long‐range stress heterogeneity imparted by the dislocations does demonstrate the mechanism by which back stress can emerge.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we note that because the microstructure and micromechanical state that persists during steady‐state creep is the end product of evolution that occurred during the preceding transient, observations of material that were either still within the transient or had reached steady‐state can both provide information on the processes occurring during the transient. For example, stress heterogeneity and associated back stress accumulate during the transient but persist at a steady‐state (Hansen et al., 2021; Wallis et al., 2020). Therefore, the presence of long‐range internal stresses in the rocks from the Oman‐UAE ophiolite supports the back‐stress model of transient creep, regardless of whether the final phase of deformation recorded by the microstructure and micromechanical fields occurred during a transient or at steady state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the degree to which GND contribute to transient creep under high-temperature, low-stress conditions is unclear. For example, in many studies on high-temperature, low-stress deformation of olivine (e.g., Bai & Kohlstedt, 1992;Darot & Gueguen, 1981;Karato & Lee, 1999;Karato et al, 1986;Karato et al, 1980), high density GNDs (far exceeding the dislocation density corresponding to the applied stress) reported by Hansen et al (2021); Wallis et al (2021) are not observed. This is likely due to the effect of dislocation recovery to form low energy configuration such as sub-boundaries and/or to the effect of dynamic recrystallization by grain-boundary migration (Karato, 1988;Karato et al, 1980Karato et al, , 1982.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Therefore one may expect creep behavior of a polycrystalline olivine similar to that of a polycrystalline ice. Indeed, strain softening is observed in some studies on olivine single crystals (e.g., Durham et al, 1979;Hanson & Spetzler, 1994), whereas strain hardening is observed in the transient creep of olivine aggregates (Chopra, 1997;Hansen et al, 2021).…”
Section: Causes For Transient Creepmentioning
confidence: 99%